2020
DOI: 10.3389/fneur.2020.580877
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Intracranial Pseudoaneurysms With a Novel Covered Stent: A Series of 19 Patients With Midterm Follow-Up

Abstract: Background: The optimal treatment for intracranial pseudoaneurysm is unclear. This study aims to analyze the outcome of treating intracranial pseudoaneurysm with a novel covered stent.Materials and Methods: The institutional imaging and clinical databases were retrospectively reviewed for patients with intracranial pseudoaneurysms treated with Willis covered stent from January 2017 to December 2019. The clinical presentations, etiology, intraoperative complications, and immediate and follow-up outcomes were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the currently available covered stents cannot usually be navigated into the ACA due to their thickness and stiffness. 15 FD can provide a >30% rate of metal coverage when fully deployed and can change the hemodynamics of the aneurysm, causing thrombosis in the aneurysm and acting as a scaffold to promote neointimal growth. 16 In a previous report and meta-analysis, FD deployment was effective for pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the currently available covered stents cannot usually be navigated into the ACA due to their thickness and stiffness. 15 FD can provide a >30% rate of metal coverage when fully deployed and can change the hemodynamics of the aneurysm, causing thrombosis in the aneurysm and acting as a scaffold to promote neointimal growth. 16 In a previous report and meta-analysis, FD deployment was effective for pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-angled view afforded by the endoscope has improved the visualization of perforating arteries, especially those arising from the posterior wall of the parent artery, so it has gradually been applied in aneurysm surgery. Understanding the relationship between the aneurysm and surrounding structures before, during, and after aneurismal clipping could help ensure adequate aneurysmal clipping [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Two case series have reported the successful treatment of traumatic ICA pseudoaneurysms with the Willis covered stent [18,19]. Covered stent implantation can immediately exclude the aneurysm from the parent artery and restore the normal blood ow.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported stent-assisted coiling treatment for intracranial pseudoaneurysms with different outcomes [6,8,10,12,13]. Flow diversion devices implantation with or without coils and covered stent implantation were reported to be effective as therapy of pseudoaneurysms [5,15,18,19]. However, the use of ow diversion devices accompanied with dual antiplatelet therapy before the procedure may be limited in patients with acute bleeding.…”
Section: Introductionmentioning
confidence: 99%